The Development of First Line Nurse Manager Competency Scale, Lerdsin Hospital - Tharee, Phiphatthananon; Nantsupawat, Apiradee; Oumtanee, Areewan (Journal of The Royal Thai Army Nurses, 2025)
This study aimed to: 1) identify key competencies of first-line nurse managers, 2) develop a competency assessment tool for first-line nurse managers, and 3) evaluate the tool’s quality at Lerdsin Hospital. The study was conducted in three phases. In Phase 1, competencies were identified through focus group discussions with 25 senior, middle, and junior-level nurse executives. Data from these discussions were analyzed to define essential competencies. Phase 2 involved developing the competency assessment tool and identifying indicative behaviors using a Likert scale. Phase 3 assessed the tool’s quality through expert content validity analysis and reliability testing among four assessor groups: supervisors, first-line nurse managers, peers, and subordinates. A total of 235 participants were selected through purposive and systematic sampling. Data from assessments were analyzed for consistency across groups using mean and standard deviation. The findings identified five key competency dimensions for first-line nurse managers at Lerdsin Hospital: 1) Leadership (five sub-competencies), 2) Management of Nursing Service Quality (six sub-competencies), 3) Resource Management (five sub-competencies), 4) Professional Ethics, Morality, and Law (three sub-competencies), and 5) Academic Knowledge, Research, Innovation, and Information Technology (three sub-competencies), totaling 22 sub-competencies. The Index of Item-Objective Congruence (IOC) ranged from .60 to 1.0, and inter-rater reliability was .86. Future research should develop a rubric-based competency evaluation tool and an online competency assessment platform.